Randomized Prospective Study Comparing Preoperative Epidural and Intraoperative Perineural Analgesia for the Prevention of Postoperative Stump and Phantom Limb Pain Following Major Amputation. Issue 4 (1st July 2001) - Lambert, A. W.; Dashfield, A. K.; Cosgrove, C.; Wilkins, D. C.; Walker, A. J.; Ashley, S.
Abstract : Background and Objectives: Acute stump pain and phantom limb pain after amputation is a significant problem among amputees with a reported incidence of phantom limb pain in the first year following amputation as high as 70%. Epidural analgesia before limb amputation is commonly used to reduce postamputation acute stump pain in the immediate postoperative period and phantom pain in the first year. We investigated whether immediate postamputation stump pain and phantom pain in the first year is reduced by preoperative epidural block with bupivacaine and diamorphine compared with intraoperative placement of a perineural catheter infusing bupivacaine. Methods: In a randomized prospective trial, 30 patients scheduled for lower limb amputation were randomly assigned epidural bupivacaine at the standard rate used in our hospital (0.166%, 2 to 8 mL/h) and diamorphine (0.2 to 0.8 mg/h) for 24 hours before and during operation (14 patients; epidural group) and 3 days postoperatively, or an intraoperatively placed perineural catheter (16 patients; perineural group) for intra and postoperative administration of bupivacaine (0.25%, 10 mL/h). All patients had general anesthesia for the amputation and were asked about stump and phantom pain in the first 3 days and then at 6 and 12 months by an independent examiner. Study endpoints were rate of stump and phantom pain, intensity of stump and phantom pain, and consumption of opioids. The groups were well matched in baseline characteristics. Results: Stump pain scores in the first 3 days were significantly higher in the perineural group compared with the epidural group ( P < .01). After 3 days, 4 (29%) patients in the epidural group and 7 (44%) in the perineural group had phantom pain ( P = .32). Numbers of patients with phantom pain for epidural versus perineural group were: 5 (63%) versus 7 (88%) ( P = .25) at 6 months; 3 (38%) versus 4 (50%) ( P = .61) at 12 months. Stump pain and phantom sensation were similar in both groups at 6 and 12 months. Conclusions: Using our regimen, perioperative epidural block started 24 hours before the amputation is not superior to infusion of local anaesthetic via a perineural catheter in preventing phantom pain, but gives better relief of stump pain in the immediate postoperative period.